Effect-based evaluation of ozone treatment for removal of micropollutants and their transformation products in waste water. Issue 10 (19th May 2021) - Dopp, Elke; Pannekens, Helena; Gottschlich, Anne; Schertzinger, Gerhard; Gehrmann, Linda; Kasper-Sonnenberg, Monika; Richard, Jessica; Joswig, Matthias; Grummt, Tamara; Schmidt, Torsten C.; Wilhelm, Michael; Tuerk, Jochen
ABSTRACT: The aim of this interdisciplinary research project in North Rhine-Westphalia (NRW), Germany, entitled "Elimination of pharmaceuticals and organic micropollutants from waste water" involved the conception of cost-effective and innovative waste-water cleaning methods. In this project in vitro assays, in vivo assays and chemical analyses were performed on three municipal waste-water treatment plants (WWTP). This publication focuses on the study of the in vitro bioassays. Cytotoxic, estrogenic, genotoxic and mutagenic effects of the original as well as enriched water samples were monitored before and after wastewater treatment steps using MTT and PAN I, ER Calux and A-YES, micronucleus and Comet assays as well as AMES test. In most cases, the measured effects were reduced after ozonation, but in general, the biological response depended upon the water composition of the WWTP, in particular on the formed by-products and concentration of micropollutants. In order to be able to assess the genotoxic and/or mutagenic potential of waste-water samples using bioassays like Ames test, Comet assay or micronucleus test an enrichment of the water sample via solid-phase extraction is recommended. This is in agreement with previous studies such as the "ToxBox"-Project of the Environmental Agency in Germany.